Cyclic stretch induces VEGFA alternative splicing via Serine/Arginine-Rich Splicing Factor 1 - Xie, Zhi-Wei; Chen, Yuan-Xiu; Long, Cai-Feng; Qi, Ying-Xin; Yao, Qing-Ping (Cellular and Molecular Biology, 2018)
Abnormal proliferation of vascular smooth muscle cells (VSMCs) induced by high cyclic stretch is crucial in the vascular remodeling during hypertension. Vascular endothelial growth factor A (VEGFA) alternative splicing plays important roles in the pathological process of vascular diseases and remodeling. However, the roles of VEGFA isoforms in modulating VSMC functions in response to cyclic stretch remain unclear. We hypothesize that high cyclic stretch may induce VEGFA alternative splicing via Serine/arginine-rich splicing factor 1 (SRSF1) which subsequently induce VSMC proliferation. In the present research, hypertensive rat model was established using the abdominal aortic constriction method. In comparison with sham-operated group, immunohistology staining showed translocation of SRSF1 into nuclei in hypertensive rat thoracic aorta, and RT-PCR detected a shift of VEGFA expression pattern, including the increased expression of VEGFA120 and VEGFA164, but not VEGFA188.Then VSMCs were subjected to cyclic stretch in vitro using a Flexercell strain unit. VEGFA ELISA assay showed 15% cyclic stretch increased the secretion of VEGFA which significantly increased proliferation of VSMCs. Western blot and immunofluorescence detected accumulation of SRSF1 in nuclei after 15% cyclic stretch application. Furthermore, SRSF1-specific siRNA transfection reversed the VEGFA secretion induced by pathological high cyclic stretch. Our present results suggested that pathologically high cyclic stretch induces the shuttling of SRSF1 which results in the secretive pattern splicing of VEGFA and finally contributes to the proliferation of VSMCs.